Theoretical Analysis on Speed Regulation of Slotted-type Eddy-current Couplers - Yang Chaojun; Yang Fan; Peng Zhizhuo; Zhu Jiwei; Hang Tian; Ding Yifei (Jixie chuandong)
Aiming at the speed regulation characteristics of slotted-type eddy-current couplers, the expression of the induced magnetic field generated by the induced eddy current is derived by using Ampère's law and the induced magnetic field is introduced into the equivalent magnetic circuit model. Then, the calculation formula of electromagnetic torque is derived in combination with Kirchhoff's law. The electromagnetic torque formula is combined with the expression of constant torque load and quadratic rate load respectively, and the theoretical formula of the speed regulation relationship under corresponding load conditions is obtained. The 3D finite element simulation and experiment are used to verify the proposed theoretical model of speed regulation. It is found that the proposed theoretical model has good accuracy in the case of small air gap length.